ANALISIS KESALAHAN BUKU MATEMATIKA MATERI RELASI DAN FUNGSI KELAS VIII SERTA ALTERNATIF PENYELESAIANNYA - Abdur Rohim (LPPM STKIP PGRI Sidoarjo, 2020)
One aspect of the 2013 curriculum that needs to be improved is textbooks. Textbooks play a role in helping teachers deliver material and can assist students in supporting the material presented by the teacher. The reality in the field is that teachers are reluctant to use students' mathematics textbooks including the 2017 revised edition of class viii semester 1 mathematics books. This is because there are still some errors and also books are still difficult for some students to understand. The purpose of this study was to analyze the errors contained in the mathematics books of class viii students regarding relations and functions. This research is a qualitative research using a descriptive research design. The validity of the data used data triangulation and referential adequacy. The results showed that there were still 6 concept errors, 2 image errors and 15 writing errors. From these findings, it can be said that the quality of this book is not yet optimal and that there is a need for improvement so that it fits the original purpose of making the book.